Anti‐inflammatory Effect of Rosmarinic Acid and an Extract of Rosmarinus officinalis in Rat Models of Local and Systemic Inflammation. (6th November 2014) - Rocha, Joao; Eduardo‐Figueira, Maria; Barateiro, Andreia; Fernandes, Adelaide; Brites, Dora; Bronze, Rosario; Duarte, Catarina MM; Serra, Ana Teresa; Pinto, Rui; Freitas, Marisa; Fernandes, Eduarda; Silva‐Lima, Beatriz; et al.
Abstract Rosmarinic acid is a polyphenolic compound and main constituent of Rosmarinus officinalis and has been shown to possess antioxidant and anti‐inflammatory properties. We aimed to evaluate the anti‐inflammatory properties of rosmarinic acid and of an extract of R. officinalis in local inflammation (carrageenin‐induced paw oedema model in the rat), and further evaluate the protective effect of rosmarinic acid in rat models of systemic inflammation: liver ischaemia–reperfusion (I/R) and thermal injury models. In the local inflammation model, rosmarinic acid was administered at 10, 25 and 50 mg/kg (p.o.), and the extract was administered at 10 and 25 mg/kg (equivalent doses to rosmarinic acid groups) to male Wistar rats. Administration of rosmarinic acid and extract at the dose of 25 mg/kg reduced paw oedema at 6 hr by over 60%, exhibiting a dose–response effect, suggesting that rosmarinic was the main contributor to the anti‐inflammatory effect. In the liver I/R model, rosmarinic acid was administered at 25 mg/kg (i.v.) 30 min. prior to the induction of ischaemia and led to the significant reduction in the serum concentration of transaminases (AST and ALT) and LDH. In the thermal injury model, rosmarinic acid was administered at 25 mg/kg (i.v.) 5 min. prior to the induction of injury and significantly reduced multi‐organ dysfunction markers (liver, kidney, lung) by modulating NF‐κB and metalloproteinase‐9. For the first time, the anti‐inflammatory potential of rosmarinic acid has been identified, as it causes a substantial reduction in inflammation, and we speculate that it might be useful in the pharmacological modulation of injuries associated to inflammation.